Factor structure and measurement invariance of the self-discipline model using the different-length questionnaires: Application of multiple matrix sampling - Suntonrapot Damrongpanit (2019)
© 2019 by authors, all rights reserved. The purposes of this study were to test the structural validity and to test the parameters invariance of the self-discipline measurement model for good student citizenship among the models, using the data from the 1,047 complete questionnaires and the reducing length questionnaires with multiple matrix sampling technique. The sample size of this study was 1,047 bachelor’s degree students selected by means of a multi-stage sampling technique. A set of 5 rating scale and 89-item questionnaires, divided into two versions, 44 and 45 each. The data were analyzed by confirmatory factor analysis and multiple group analysis. The research findings were as follows: 1) the model can be used to confirm the self-discipline construct validity of 4 components as responsibility, honesty, compliance and patience with ambition and intention, and 2) patterns and parameters of the model were varied between the models using the data from the full questionnaire and the data that reduced the length of the questionnaire. However, the measurement model is consistent with the empirical data in both cases.